Atomic layer deposition enables multi-modal three-dimensional electron microscopy of isoporous membranes. Issue 7 (25th January 2023) - Simon, Assaf; Zhang, Zhenzhen; Abetz, Clarissa; Abetz, Volker; Segal-Peretz, Tamar
Abstract : 3D understanding of block copolymer membranes is challenging due to the lack of inherent contrast between the blocks. Selective growth of AlO x within the pore-forming domain achieved stable contrast enhancement and enabled 3D characterization. Abstract : Block copolymers (BCPs) are promising materials for water purification. They enable the fabrication of integral asymmetric isoporous membranes with high permeability and good selectivity. Commonly, the characterization of such hierarchical structures is performed by conventional electron microscopy (EM) means, namely scanning and transmission electron microscopy (SEM and TEM, respectively). However, due to the inherent lack of contrast between BCP domains, external contrast agents are required to achieve informative, high-resolution imaging. In addition, such EM techniques are typically limited to a certain cross-section or surface morphology only. In this paper, we harness the selective growth of AlO x in the pore-forming domains of BCPs to create an internal and stable contrast difference between the blocks. This in turn allowed us to perform advanced three-dimensional characterization of the membranes with focused ion beam (FIB)-SEM and TEM tomography, providing an understanding of the 3D structure and properties such as 3D geometry of the pores, 3D tortuosity, and 3D permeability. This 3D characterization also provides better correlations between the membrane structure and its performance. Such knowledge can allow better design and fine-tuning of BCP membranes and other membranes for their applications.